A Novel Approach of In-Situ Electrobiosynthesis of Metal Oxide Nanoparticles Using Crude Plant Extract as Main Medium for Supporting Electrolyte - Norzahir, Sapawe; Mohd Ariff, Rustam; Muhammad Hafizan Hakimin, Mahadzir; Mohamad Kamal Ezzat, Mohamad Lani; Azizzami, Raidin; Muhammad Farhan, Hanafi (Elsevier Ltd., 2019)
The release of dyes into the environment during textile fibre dyeing and finishing processes is a main source of water pollution. There is a need to look for effective treatment processes to overcome this problem. Photocatalytic method becomes the most effective to remove the dyes. In this study, in-situ electrobiosynthesis of various metal oxide such as silver oxide (AgO), copper oxide (CuO), zinc oxide (ZnO), and nickel oxide (NiO) using plant extract as new green electrolyte was performed with enhancement behaviour and structural of the catalyst for excellent photodegradation of malachite green (MG) dye from aqueous solution. The MG was successfully degraded at optimum condition of 10 mg/L of initial concentration with 0.5 g/L of catalyst dosage of AgO, CuO, ZnO, and NiO; at pH of 2 under visible light irradiation within 1 hour of contact time at room temperature which were 91.7 , 94.0, 98.5 , and 97.3 , respectively. Therefore, the effectiveness of eelctrobiosynthesis of AgO, CuO, ZnO, and NiO metal catalyst via electrochemical method using 100 crude plant extract as new supporting electrolyte was established and confirmed through this study. The synthesized metal oxide catalyst has a great potential as a photocatalyst in photocatalytic reaction for degradation of organic pollutants in wastewater.